A Case Report of Complete Resolution of Auricular Mucormycosis in an 18-Month-Old Diabetic Child - Mariam Aljehani; Hatem Alahmadi; Mansour Alshamani (Case Reports in Otolaryngology)
Background. One of the most rare but deadly types of infectious fungal infection is Mucormycosis. All the cases reported with this type of infection are immunocompromised individuals. The challenge of early detection and intervention makes it one of the high mortality rates among other infectious diseases. Case Report. We report an 18-month-old girl with undiagnosed diabetes presented with a very aggressive form of necrotic infection of the ear auricle with facial nerve palsy. Using a series of magnetic resonance imaging, antibiotics, and high clinical suspicion, a diagnosis was established, and the patient was sent to the operation theatre for surgical debridement. Monthly follow-ups showed improvement of the facial palsy, and a plan for artificial auricle is set to occur in the following months before the age of five. Discussion. Mucormycosis is considered a very fatal and aggressive infection that has a very high mortality rate in immunocompromised patients. Early detection of such cases with an array of magnetic resonance imaging (MRI) and computed tomography (CT) is crucial in early treatment. Early aggressive surgical debridement and empirical coverage of bacterial, viral, and fungal infections can also alleviate the chances of preventing any secondary infection to develop in such cases. Conclusion. A combination of antifungal, antibiotic, and antiviral with timely surgical intervention improved the patient with complete resolution of the facial nerve palsy and no further recurrence of the infection.